Round-the-Year Fodder Availability fom Maize - Chaudhary, Dharam Paul (Indian Farming, 2015)
Maize is an excellent crop which could effectively be utilized as fodder. Specialty corn is going to play an important role in the socio-economic perspective of the farmers. Baby corn and sweet corn cultivation will substantially add up to the income of the farmers as specialty corn is sold at reasonably good price in the market, whereas, the green fodder will boost the dairy farming. The silage making is a breakthrough technology which could provide a quantum boost to the dairy sector. Lastly, the urea treatment of maize stover is another simple technique, suitable for small and marginal farmers. By employing these technologies, the farmers can easily enhance the milk production potential of their cattle.